IMPLEMENTASI MODEL BERAMEAN UNTUK MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR KRITIS SISWA SDN MELAYU 2 BANJARMASIN - Steven Riyadh Akbar; Akhmad Riandy Agusta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem faced in this research is the low level of activity and critical thinking skills of students in learning mathematics. This happens because the learning carried out is one-way, there is a lack of active participation of students during learning, there is no variation in the use of learning models and media, and students have not mastered critical thinking indicators. One of the proposed solutions is to apply the BERAMEAN model. This research aims to increase students' critical thinking activities and skills. The method used is Classroom Action Research (PTK). The research subjects were 20 fifth grade students at SDN Melayu 2 Banjarmasin. The data collected is qualitative data. The results showed that student activity increased from 30% at the first meeting to 100% at the fourth meeting. Students' critical thinking skills also increased from 25% at the first meeting to 95% at the fourth meeting. Based on these results, it can be concluded that the use of the BERAMEAN model is effective in increasing students' critical thinking activities and skills.